Theories and Contemporary Development of Organizational Perspectives in Social Sciences. Feminist approach to organizational analysis. Part 3 - Mediani Bhandari (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
This paper is purely theoretical in which I have illustrated the contributions of the founding theorist of Western sociology, by focusing on how they addressed (or didn’t address) organizations. Then, I have discussed (in brief) the development of organizational theory and how organizational theorists are responding to the emergence of challenges to the traditional rational approaches to understanding organizations. These analyses are situated on the historical contexts include major contributions of each theorist. This research is solely based on the secondary information. Paper contents four Sections: first the work of the three founding theorists of Western Sociology, Karl Marx; Émile Durkheim and Max Weber, secondly, I have exemplified the development of organizational theory and the emergence of challenges to the traditional rational approaches to understand the organization; where I have analyzed the work of Classical theorists- Max Weber, Henri Fayol, Frederick Taylor, Luther Halsey Gulick, Herbert A. Simon, Berton H. Kaplan, modern theorist- Michel Foucault, Jurgen Habermas, Jacques Derrida, Jurgen Habermas etc. Third Section covers the contemporary theories and perspectives. In this section I have exemplified how Philip Selznick, Peter Blau, James David Thompson and Charles Perrow incorporated the Weber notion of bureaucracy followed by DiMaggio, Paul, J. and Walter W. Powell etc. and in forth section, covers the feminist approach in theory building with focus of organizational analysis (with the focus of Arlene Daniels, Dorothy Smith, Marjorie DeVault, Gisela Bock and Susan James, Martha Calas, Linda Smircich etc. work). This paper has detailed footnotes quoted from the original sources and contents useful reference of the sociological theory and practices for concerned social scientist to build their knowledge base and research direction.